2015
DOI: 10.3389/fnbeh.2015.00087
|View full text |Cite
|
Sign up to set email alerts
|

Interaction effect between handedness and CNTNAP2 polymorphism (rs7794745 genotype) on voice-specific frontotemporal activity in healthy individuals: an fMRI study

Abstract: Recent neuroimaging studies have demonstrated that Contactin-associated protein-like2 (CNTNAP2) polymorphisms affect left-hemispheric function of language processing in healthy individuals, but no study has investigated the influence of these polymorphisms on right-hemispheric function involved in human voice perception. Further, although recent reports suggest that determination of handedness is influenced by genetic effect, the interaction effect between handedness and CNTNAP2 polymorphisms for brain activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 62 publications
(104 reference statements)
0
15
0
Order By: Relevance
“…Further evidence for atypical lateralization for language associated with CNTNAP2 polymorphisms comes from a study of language, voice, and general auditory processing. Koeda et al () reported increased activation in the right middle frontal gyrus during native language listening in Japanese carriers of the nondominant allele for rs7794745. This pattern of increased right hemisphere activation also held for human voice perception (reversed sentences) the right middle frontal gyrus.…”
Section: Developmental Language Disordermentioning
confidence: 99%
“…Further evidence for atypical lateralization for language associated with CNTNAP2 polymorphisms comes from a study of language, voice, and general auditory processing. Koeda et al () reported increased activation in the right middle frontal gyrus during native language listening in Japanese carriers of the nondominant allele for rs7794745. This pattern of increased right hemisphere activation also held for human voice perception (reversed sentences) the right middle frontal gyrus.…”
Section: Developmental Language Disordermentioning
confidence: 99%
“…Neuroimaging studies have supported the notion that these common variants play a role in psychiatric disorders. SNP rs2710102 has been implicated in brain connectivity in healthy individuals [16, 18, 19], and rs7794745 was implicated in audio-visual speech perception [69], voice-specific brain function [22], and was associated with reduced grey matter volume in left superior occipital gyrus [20, 21]. These studies focused principally on language tasks in general population, given the reported suggestive implications of CNTNAP2 in language impairment traits of ASD or language-related phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in subsequent studies, rs2710102 was implicated in early language acquisition in the general population [15], and showed functional effects on brain activation in neuroimaging studies [16-19]. Furthermore, genotypes at rs7794745 were associated with reduced grey matter volume in the left superior occipital gyrus in two independent studies [20, 21], and alleles of this SNP were reported to affect voice-specific brain function [22]. Genetic associations with ASD for these, and several other SNPs in CNTNAP2 , have been reported in a number of studies [23-28].…”
Section: Introductionmentioning
confidence: 99%
“…3 ), association studies may help to narrow down and to better circumscribe the phenotypic scope of CNTNAP2 function. For instance, CNTNAP2 polymorphisms may affect neural development as related to vocal communication and language processing [Koeda et al, 2015]. The genotype of SNP rs7794745 (A/A or A/T) in intron 2 significantly affects voice-specific brain function in the right middle frontal gyrus and in the bilateral superior temporal gyrus in healthy individuals [Koeda et al, 2015].…”
Section: The Phenotypic Scope Of Cntnap2 Deletion Disordersmentioning
confidence: 99%
“…For instance, CNTNAP2 polymorphisms may affect neural development as related to vocal communication and language processing [Koeda et al, 2015]. The genotype of SNP rs7794745 (A/A or A/T) in intron 2 significantly affects voice-specific brain function in the right middle frontal gyrus and in the bilateral superior temporal gyrus in healthy individuals [Koeda et al, 2015]. The SNP rs2710102 in intron 13 of CNTNAP2 associates with impaired language development, specific language impairment, delayed oral and written language skills, dyslexia, age of first words as well as speech and sound disorder ( Fig.…”
Section: The Phenotypic Scope Of Cntnap2 Deletion Disordersmentioning
confidence: 99%